A critical realist theory of sport - Scambler, Graham, author.
1 online resource (188 pages).
Keywords: "This book argues that sport in the era of global or financialised capitalism has undergone a process of fracturing, which requires a re-assessment of longstanding and consensual accounts of traditional-to-modern sporting activity. Considering rival concepts of sport, it presents detailed, illustrative studies of various types of sporting or athletic activity - including soccer, cricket, rugby and track and field - to advance an alternative sociological understanding of sport rooted in the philosophies and theories of critical realism and critical theory. As such, A Critical Realist Theory of Sport will appeal to scholars of sociology and social theory with interests in sport, research methods and critical realist thought"--